Population Education in Asia and the Pacific. Bulletin of the Unesco Regional Office for Education in Asia and the Pacific. Number 23, June, 1982 - United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific; United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The necessity of successfully managing population and development to ensure the quality of life in Asia in the coming decade is emphasized in this bulletin, which is arranged into four sections. Section one contains an article dealing with change and development of population education in Asia and the Pacific and a demographic analysis. Section two consists of country reports prepared by the directors of national population education projects and updated papers presented at workshops held in Bangkok in 1981 and in Suva in 1979. Countries reported on are Afghanistan, Bangladesh, China, India, Indonesia, Malaysia, Nepal, Pakistan, the Philippines, Korea, Viet Nam, Sri Lanka, Thailand, Turkey, Fiji, Papua New Guinea, Solomon Islands, Tonga, and the Trust Territory of the Pacific Islands. A synthesis of innovative experiences in population education concludes the second section. Section three deals with quality of life themes as related to population, including agriculture and food, nutrition and health, resources and the environment, growth and employment, migration and urbanization, socio-economic development, and sociocultural values. The publication concludes with a bibliographic supplement on population education. (RM)
Availability: UNIPUB, 1180 Avenue of the Americas, New York, NY 10036 ($27.50).
ERIC Note: Some tables, figures, and photographs may not reproduce clearly in microfiche.
Microfiche.
Keywords: Adult Education; Agriculture; Comparative Education; Demography; Developing Nations; Economic Development; Educational Development; Educational Innovation; Employment; Environmental Influences; Food; Foreign Countries; Migration Patterns; Nutrition; Population Distribution; Population Education; Population Growth; Population Trends; Quality of Life; Social Values; Urbanization; Asia -- Pacific Region; Information Analyses; Books